Mineralogical and geochemical characterization of the Au-Ag vetiform mineralization of the Aserradero Stream, municipality of California, Santander (Colombia): geometalurgic implications (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
The mining district of Vetas-California is a mining reference in the Santander massif, characterized by the presence of hydrothermal and porphyry mineralizations. A series of vetiform and brechoid mineralizations develop near the La Baja brook under a structural domain related to local tectonic structures as La Baja, Móngora and Angosturas faults and associated minor faults. In the study area there are 22 veins parallel to each other with a NE heading and diving 75-80° to the North. Based on the mineralogical analysis performed on six thin sections by means of optical microscopy and scanning electron microscopy along with the diffraction analysis of X-ray this deposit is classified as medium to high sulfidation hydrothermal. Hydrothermal alteration minerals include quartz, clays (illite and kaolinite), pyrite, sericite, muscovite and alunite. The phases of hydrothermal alteration include argillic, advanced argillic, silicification and phyllic. Au-Ag mineralization is associated with alteration argillic and phyllic. The optimum degree of release for pyrite was achieved with 100 mesh, this result was obtained from the grinding of the mineral head and its analysis under a microscope. The presence of clay minerals from the kaolinite group, predominantly dickite, represents an inconvenience to achieve an effective milling and flotation process due to the decrease in the flow of the mineral processing, decrease in the recovery of minerals of interest due to a consequent increase in viscosity. In addition, its presence implies a greater economic expense due to the need to use reagents for the flotation process and tailings thickening. The hydrothermal system was derived from an alkaline tracing magma and the deposit is defined as an alkaline rock-hosted medium to high sulfur hydrothermal gold deposit.
Keywords: genetic profile